Atomic layer deposition of palladium nanoparticles on a functional electrospun poly-cyclodextrin nanoweb as a flexible and reusable heterogeneous nanocatalyst for the reduction of nitroaromatic compounds. Issue 10 (18th September 2019) - Topuz, Fuat; Uyar, Tamer
Abstract : The production of a Pd nanoparticle-decorated electrospun poly-cyclodextrin nanoweb by atomic layer deposition for its use in the reduction of nitroaromatics. Abstract : We here show a rational approach for the fabrication of a flexible, insoluble catalytic electrospun nanoweb of cross-linked cyclodextrin (CD) for the reduction of nitroaromatics. CD nanofibers were produced by electrospinning an aqueous HP-β-CD solution containing a multifunctional cross-linker ( i.e., 1, 2, 3, 4-butanetetracarboxylic acid, BTCA) and were subsequently cross-linked by heat treatment, which led to an insoluble electrospun poly-CD nanoweb. The poly-CD nanoweb was decorated with Pd nanoparticles (Pd-NPs) by atomic layer deposition (ALD) technique over 20 cycles to give rise to a catalytic electrospun nanoweb ( i.e., Pd@poly-CD). The formation of the Pd-NPs on the poly-CD nanofiber surface was clearly evidenced by TEM and STEM imaging, which displayed the homogeneously distributed Pd-NPs with a mean size of 4.34 nm. ICP-MS analysis revealed that the Pd content on the Pd@poly-CD nanoweb was 0.039 mg per mg of nanoweb. The catalytic performance of the Pd@poly-CD nanoweb was tested for the reduction of a nitroaromatic compound ( i.e., 4-nitrophenol (4-NP)), and high catalytic performance of the Pd@poly-CD nanoweb was observed with a corresponding TOF value of 0.0316 min −1 . XPS was used to explore the oxidation state of Pd atoms before and after the catalytic reduction of 4-NP, and no significant change was observed after catalytic reactions. In brief, the Pd@poly-CD nanoweb having handy, flexible, structural stability and reusability can be effectively used in environmental applications as a heterogeneous nanocatalyst for the reduction of toxic nitroaromatics.